Nano spaces via á¼¿-semi-g-Closed Set - Jalil, Maher Abdul; Ibrahim, Ahmed (Iraqi Journal of Science, 2020)
In this research and by using the concept of , a new set of near set which is nano-á¼¿-semi-g-closed set was defined. Some properties and examples with illustrative table and an applied example were presented.